The talent identification of kayak athletes: A research-based on analytic hierarchy process - Nur Yasin, S.; Ma`mun, A.; Rusdiana, A.; Gafar Abdullah, A.; Nur, L. (International Journal of Human Movement and Sports Sciences, 2020)
This research aimed to identify the talent needed by kayak athletes between 14-16 years old. Furthermore, the data gathered in this study would be analyzed by using the Analytic Hierarchy Process (AHP) in order to find out which element has significant roles in supporting kayak athletes. Mixed-Method Research (MMR) was employed in this research by using a literature study and administering a questionnaire to 32 professional coaches consisting of twenty eight male and four female coaches. The rationale for selecting these coaches is to identify their opinions regarding the talent criteria of selecting kayak athletes. The result of the analysis showed that there were five parameters that could be used to identify the talent of kayak athletes, such as anthropometry (height and weight), biomechanics (endurance and strength), psychology (self-confidence and focus), special endurance (aerobic and anaerobic; physiology), and skills (catch and pull-push). This talent identification model provides information for coaches, athletes, and parents to find out the talent of kayak athletes.